The public-private partnership (PPP) initiative in healthcare system: as the pathways to achieve the SDGs in Nepal - Bhatt, Laxman Datt; Shrestha, Ramesh; Bhandari , Ved Prasad (Europasian Journal of Medical Sciences, 2021)
Globally, financing healthcare is one of the biggest challenges and it becomes a life or death issue in poor countries. Nepal is strongly committed to universal health coverage and Sustainable Development Goals. Existing public health services are inadequate to cater to the growing demands of quality health care and Public Private Partnership (PPP) evolved as newer arrangement for robust healthcare system, improved healthcare quality and enhance cost-effectiveness. Nepal has successfully utilized the PPP model in multiple sectors, however there is limited experience in healthcare. Strengthening PPP models in healthcare could be the pathway for Nepal toward SDG’s and UHC achievement. DOI: https://doi.org/10.46405/ejms.v3i2.266